2017
DOI: 10.1016/j.bone.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and systemic regulation of sclerostin

Abstract: The Wnt/β-catenin signaling pathway plays an essential role in osteoblast biology. Sclerostin is a soluble antagonist of Wnt/β-catenin signaling secreted primarily by osteocytes. Current evidence indicates that sclerostin likely functions as a local/paracrine regulator of bone metabolism rather than as an endocrine hormone. Nonetheless, circulating sclerostin levels in humans often reflect changes in the bone microenvironment, although there may be exceptions to this observation. Using existing assays, circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 114 publications
(129 reference statements)
8
45
0
3
Order By: Relevance
“…Several clinical factors associated with sclerostin production and serum sclerostin levels have been identified other than renal dysfunction in non-CKD subjects, including age, BMI, diabetes, estrogen, and PTH [34,35]. Relevant to our result is the previous finding that estrogen was associated with serum sclerostin levels [36]. Since most of our MHD patients were postmenopausal and estrogen levels in postmenopausal women are lower than in men of a similar age, serum sclerostin levels may be lower in females than males.…”
Section: Discussionsupporting
confidence: 58%
“…Several clinical factors associated with sclerostin production and serum sclerostin levels have been identified other than renal dysfunction in non-CKD subjects, including age, BMI, diabetes, estrogen, and PTH [34,35]. Relevant to our result is the previous finding that estrogen was associated with serum sclerostin levels [36]. Since most of our MHD patients were postmenopausal and estrogen levels in postmenopausal women are lower than in men of a similar age, serum sclerostin levels may be lower in females than males.…”
Section: Discussionsupporting
confidence: 58%
“…As described above, SOST has emerged as an endocrine factor that regulates glucose and fat metabolism . Outside of the skeleton, SOST is present in the serum, supporting a circulating endocrine role . Circulating SOST increases progressively with age and the higher serum SOST levels found in elderly postmenopasual women are associated with a greater risk of hip fractures .…”
Section: Wnt Signaling In Aging Adipose Tissuementioning
confidence: 94%
“…Given increasing evidence that sclerostin modulates not only bone formation, but also bone resorption (Tu et al 2015), these findings suggest that sclerostin may be in the pathway of estrogen action on bone, as shown further by the mouse models discussed later. Moreover, similar to the translation of RANKL inhibition to a new therapeutic, sclerostin inhibition using a humanized monoclonal antibody, romosozumab (Cosman et al 2016), results in a profound increase in bone formation and reduction in bone resorption in postmenopausal women, qualitatively similar to the pattern of changes in bone turnover induced by estrogen treatment (Drake and Khosla 2017). …”
Section: Human Studiesmentioning
confidence: 95%
“…There is also considerable evidence from human studies that estrogen regulates the production of the proposed inhibitor of Wnt signaling, sclerostin (Drake and Khosla 2017). A number of studies have shown that treatment of postmenopausal women with estrogen (Modder et al 2011a,b; Fujita et al 2014; Farr et al 2015) or with the selective ER modulator, raloxifene (Chung et al 2012), reduces circulating sclerostin levels using several different assays for sclerostin.…”
Section: Human Studiesmentioning
confidence: 99%